"Rise Up, Hand in Hand": Early Childhood Teachers Writing a Liberatory Literacy Pedagogy. (June 2023) - Machado, Emily; Beneke, Maggie R.; Taitingfong, Jordan
Although writing is often used for personal reflection in teacher education, it is less commonly leveraged to imagine educational futures (Gilligan, 2020)—particularly those centered on collective liberation. Amid intersecting social crises, however, imagining futures is critically important (Ladson-Billings, 2021), and writing is a crucial step toward bringing them into the present. In this participatory case study (Reilly, 2010), we explored the future-oriented writing practices of five early childhood teachers in an inquiry group. Drawing on critical literacy (Vasquez et al., 2019) and prolepsis (Cole, 1993), we describe how collaborative, creative, and pedagogical writing supported them in envisioning, enacting, and leading liberatory literacy pedagogies within and beyond their schools. Findings contribute to literature in teacher education, early childhood education, and literacy.